The 'cinematic poetry' of the Thaw. (2nd January 2018) - Thorsen, Elise
Abstract: As represented in Soviet cinema from Stalinism to the Thaw, the ability to appreciate and recite poetry was a meaningful characteristic of a positive hero. However, the way this positive characteristic was reflected on the screen shifted drastically. In part, this shift reflected familiar Thaw priorities of emphasizing sincerity and the individual experience in re-presenting the tropes of Stalinism. However, shifts in performance also responded to the long-standing tension in Russian culture between the value and the potential banality of kul'turnost', a tension that had been less prominent in Stalinist culture, even as the Stalinist valorisation of education resulted in its emerging more strongly than ever in post-Stalinist cinema. This article examines three sites of post-Stalinist cinema that illustrate how this tension was negotiated: playful and ironic performance; unpolished but highly expressive poetry; and disjunctures in cinematic space around performed poetry.